A Study on Fatigue Management of Aviation Maintenance Mechanics-Focusing on Shift Workers - Chun-Yong Kim; Se-Jong Choi (Hanggong uju uihakoeji, 2020)
In the case of aviation maintenance work, several kinds of shift works are performed during day and night, and a lot of works are performed on the ramp due to the characteristics of the aircraft flight schedule. Maintenance workers are often exposed to the sun or in cold temperatures for aircraft maintenance works. The fatigue risk of the maintenance workers will be weighted. In particular, the work at night shift under normal biological rhythms can make maintenance workers feel sleepy during daytime work. It can also affect the safety of aircraft and individual workers. Accordingly, this study will consider fatigue-related previous researches in the field of aviation maintenance, review the effects of shift work, and how fatigue affects aviation mechanics during the day/night shifts. Considering these factors, we tried to present a plan that can minimize the fatigue of aviation workers through this study.